Development of innovative thinking of students through the solution of functional equations - Чашечникова, Ольга Серафимівна; Панченко, Тетяна Іванівна (Pedagogy of Higher and Secondary Education, 2013)
Chashechnikova O. S., Panchenko T. I. Development of innovative thinking of students through the solution of functional equations. The article is devoted to the theoretical and methodological bases for formation and development of the creative thinking in differentiated teaching of mathematics. On the basis of functional equations solution analysis, the possibilities of their performance influence on the development of learners’ innovative thinking are demonstrated.